Residential Mobility, Life Cycle Stages, Housing and the Changing Social Patterns in Reykjavik, 1874 to 1976 - Reynarsson, Bjarni (2014)
238 p. Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 1980. The main objective of this research is to explain the complex residential mobility pattern in Reykjavik, Iceland, a medium sized city, using the life cycle model. The period under study is 1974 to 1976 and the basic research approach is ecological. The main data source is all change of address forms for the Reykjavik area in 1974. The aggregated zonal flows of all moving households are broken into life cycle groups and related subsets. The spatial patterns of these flows are analyzed and the association with the social mosaic of the city. The family life cycle model was chosen as the main theoretical base for the research, because it has been proven in numerous studies to be the single most powerful model developed to explain residential mobility. It is hoped that this research will be a contribution to residential mobility theory in at least two ways: by testing the usefulness of a modified life cycle model in explaining residential mobility outside the United States and demonstrating the importance of including non-family type households in relation to the model, and by the comprehension of the role residential movements have on changing the social-demographic patterns of cities. In general, the modified household life cycle model is a much better tool for explaining the complex mobility pattern in the Reykjavik area than expected. The only serious residual from the model is a low turnover rate in a new suburban apartment house area in 1974, but when the mobility rates for that area were calculated for the next four years a rapid increase in turnover was evident as expected. The turnover rate of neighborhoods is found to go in cycles based on age and type of houses. Other findings include the following: (1) Households in the Reykjavik area are relatively mobile even by North American standards, which can be seen from the fact that 13 percent moved within the Reykjavik area in 1974. (2) New housing is the single most important factor ...